Pengaruh Budaya Organisasi dan Kompetensi terhadap Kinerja Karyawan di Perumda Air Minum Kota Padang - Genodia Zikrulloh; Eka Mariyanti (CV. ITTC INDONESIA, 2024)
The objective of this study is to examine the impact of organisational culture and competence on employee performance at Perumda Air Minum Kota Padang. This study employs a quantitative methodology, with a population comprising 220 employees. The research sample consisted of 113 employees, as determined by the Krejcie and Morgan table. The objective of the data analysis was to ascertain the extent to which organisational culture and competence influence employee performance within this organisational context. The findings indicate that organisational culture exerts a positive and statistically significant impact on employee performance at Perumda Air Minum Kota Padang. This indicates that employees who operate within a positive organisational culture tend to demonstrate enhanced performance. However, the study also revealed that competence does not exert a positive and significant influence on employee performance. This finding indicates that although competence is an important factor, organisational culture is the determining factor in the performance of Perumda Air Minum Kota Padang employees. The study's recommendation is that organisations should prioritise the reinforcement and sustenance of a positive organisational culture. This may be achieved by encouraging employees to prioritise accuracy in their work, to foster the development of robust teams and to maintain a meticulous attention to detail. Furthermore, it is essential to implement strategies that facilitate the strengthening of teamwork, the respect of diverse opinions and the concentration of efforts on the attainment of objectives. These measures are anticipated to have a beneficial impact on employee performance, to foster a productive work environment and to enhance organisational effectiveness..